الف)
$P(A) = \frac{{\left( {\begin{array}{*{20}{c}} 4 \\ 1 \end{array}} \right)\left( {\begin{array}{*{20}{c}}
3 \\ 1 \end{array}} \right)\left( {\begin{array}{*{20}{c}}
2 \\ 1 \end{array}} \right)}}{{\left( {\begin{array}{*{20}{c}}
9 \\ 3 \end{array}} \right)}} = \frac{{24}}{{84}} = \frac{2}{7}$
ب)
$P(B) = \frac{{\left( {\begin{array}{*{20}{c}}
2 \\ 1 \end{array}} \right)\left( {\begin{array}{*{20}{c}}
7 \\ 2 \end{array}} \right) + \left( {\begin{array}{*{20}{c}}
7 \\ 3 \end{array}} \right)}}{{\left( {\begin{array}{*{20}{c}}
9 \\ 3 \end{array}} \right)}} = \frac{{77}}{{84}} = \frac{{11}}{{12}}$